Metal-free double azide addition to strained alkynes of an octadehydrodibenzo[12]annulene derivative with electron-withdrawing substituents - Takeda, Naoki; Akasaka, Shuichi; Kawauchi, Susumu; Michinobu, Tsuyoshi (Beilstein Journal of Organic Chemistry, 2024)
Strain-promoted azide–alkyne cycloaddition (SpAAC) is a powerful tool in the field of bioconjugation and materials research. We previously reported a regioselective double addition of organic azides to octadehydrodibenzo[12]annulene derivatives with electron-rich alkyloxy substituents. In order to increase the reaction rate, electron-withdrawing substituents were introduced into octadehydrodibenzo[12]annulene. In this report, the synthesis of new octadehydrodibenzo[12]annulene derivatives, regioselective double addition of organic azides, and an application to crosslinking polymers are described.
Keywords: annulene; click chemistry; polymerization; strain-promoted azide–alkyne cycloaddition